Bank funding structures and risk: Evidence from the global financial crisis - Vazquez, Francisco; Federico, Pablo (Journal of Banking & Finance, 2015)
This paper analyzes the evolution of bank funding structures in the run up to the global financial crisis and studies the implications for financial stability, exploiting a bank-level dataset that covers about 11,000 banks in the U.S. and Europe during 2001–09. The results show that banks with weaker structural liquidity and higher leverage in the pre-crisis period were more likely to fail afterward. The likelihood of bank failure also increases with pre-crisis bank risk-taking. In the cross-section, the smaller domestically-oriented banks were relatively more vulnerable to liquidity risk, while the large cross-border (Global) banks were more vulnerable to solvency risk due to excessive leverage. In fact, a 3.5 percentage point increase in the pre-crisis capital buffers of Global banks would have caused a 48 percentage point in their probability of failure during the crisis. The results support the proposed Basel III regulations on structural liquidity and leverage, but suggest that emphasis should be placed on the latter, particularly for the systemically-important institutions. Macroeconomic and monetary conditions are also shown to be related with the likelihood of bank failure, providing a case for the introduction of a macro-prudential approach to banking regulation.